Protagonists of change: political identities and participation of Spanish youth in elections, 1982-2016 - Espí-Hernández, Alejandro (Acciones e Investigaciones Sociales, 2019)
In this study we look at several variables that help us understand the level of participation of Spanish youth throughout the current period of democracy, and also their political preferences. On the basis of our hypothe- ses, indicators of participation in elections reveal that Spanish young people participate in general elections to a lesser extent than adults and are slightly to the left with respect to the other age groups. As regards party preferences, the study shows that the various mutations in political colour that have taken place in Spain coincide with a change of party preference among young people but not with any increase in their participation in elections. Regarding the latter, we found a suggestion of “structural abstentionism” among the young electorate. The study reveals a disinterest in politics among young Spaniards, accompanied by abstention with an optional component. We conclude by demonstrating the key role played by young people in the alter- nation of power in Spain between 1982 and 2016.
Keywords: young people; youth; Spain; political participation; political parties; elections